INTERAKSI MASYARAKAT KOMUNITAS ISLAM BLANGKON DAN KOMUNITAS MUHAMMADIYAH DI DESA PEKUNCEN, KECAMATAN JATILAWANG, KABUPATEN BANYUMAS - Wahyu W, Anindya (Solidarity: Journal of Education, Society and Culture, 2013)
Blangkon and Muhammadiyah Islamic societies in the village Pekuncen are two communities living in the same area . Islam equations and differences in the way the ritual between the Muslim community raises Blangkon with Muhammadiyah community stereotypes of social interaction in the community . The research method used was a qualitative research method with phenomenological approach . Subjects in this study were four men and three Muslim community Blangkon Muhammadiyah society . Research sites in the Village Pekuncen , District Jatilawang , Banyumas regency . Data collection techniques used were observation , interview and documentation . The validity of the data used is an extension of the observations , increasing persistence , data triangulation and member checks . Techniques of data analysis including data collection , data reduction , data presentation , and verification . The results showed that the social interaction that occurs between the Islamic community Blangkon with the community in the village of Muhammadiyah Pekuncen shown walking in harmony with the various religious rituals were held . Respect and tolerance shown when Islam is being held ritual Blangkon perlon and appreciate Muhammadiyah are praying pose a harmonious society Pekuncen village . Constraints in interacting sentiment embodied in nature that are below the surface latent like gossip.